2018
DOI: 10.1103/physrevb.97.224104
|View full text |Cite
|
Sign up to set email alerts
|

Polarization fluctuations in the perovskite-structured ferroelectric AgNbO3

Abstract: Perovskite-structured AgNbO 3 is a promising lead-free ferroelectric material that at room temperature exhibits weak ferroelectric behavior with a large polarization under an applied electric field. Here we report first-principles molecular dynamics (FPMD) simulations of monocrystalline AgNbO 3 over a range of temperatures to examine the microscopic polarization switching mechanism. Polarization switching is found to occur at temperatures around 200 K and above; regardless of whether the simulations commence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
3
4
0
3
Order By: Relevance
“…In other words, the virgin microstructure would include two kinds of polar domains with different electric dipole arrangement types in the same Pmc2 1 symmetry, which can be regarded as polar ferroelectric and polar ferrielectric (i.e., a noncompensated antiferroelectric). This suggestion is also supported by the simulations carried out by Moriwake et al, 77 which indicated that the polar ferrielectric phase has the same space group, Pmc2 1 , as the polar phase, but it is characterized by a slightly different ion arrangement that makes its distinction difficult in microscopy and diffraction techniques. Fig.…”
Section: Ferroelectric Properties and Eld-induced Transitionssupporting
confidence: 53%
See 1 more Smart Citation
“…In other words, the virgin microstructure would include two kinds of polar domains with different electric dipole arrangement types in the same Pmc2 1 symmetry, which can be regarded as polar ferroelectric and polar ferrielectric (i.e., a noncompensated antiferroelectric). This suggestion is also supported by the simulations carried out by Moriwake et al, 77 which indicated that the polar ferrielectric phase has the same space group, Pmc2 1 , as the polar phase, but it is characterized by a slightly different ion arrangement that makes its distinction difficult in microscopy and diffraction techniques. Fig.…”
Section: Ferroelectric Properties and Eld-induced Transitionssupporting
confidence: 53%
“…14(a)-(c) further illustrate the ordering of electric dipole arrangements resulting in AFE Pbcm, FIE Pmc2 1 and FE Pmc2 1 structures, respectively. 77 Most recently, domain structure observation on AgNbO 3 single crystals, has also revealed the existence of polar domains, which would further support the deduction. 79 In this structural context, the current peak P 1 corresponds to the switching of the polar domains in non-centrosymmetric Pmc2 1 symmetry.…”
Section: Ferroelectric Properties and Eld-induced Transitionsmentioning
confidence: 62%
“…Neste sentido, estudos recentes reportados em sistemas cerâmicos a base de AgNbO3 revelaram valores de densidade de armazenamento de recuperável em torno de 1,6-2,1 J/cm 3 , quando submetidos a campos elétricos no intervalo de 175-220 kV/cm [59,60], polarização máxima de 52 C/cm 2 e polarização remanescente de 0,05 C/cm 2 na ausência de campo elétrico [44]. Além disso, a eficiência energética alcançada na cerâmica AN pura foi em torno de 37-40 %, valor este que deve ser melhorado para diminuir as perdas de energia [59,61].…”
Section: Antiferroeletricidadeunclassified
“…Fonte:[41].Entretanto, a natureza centrosimétrica do grupo espacial Pbcm não conseguiu explicar a polarização espontânea fraca (PS = 0,041 C/cm 2 ) induzida na cerâmica de AgNbO3[38]. No entanto, em 2011, com base em uma análise abrangente da estrutura, Yashima e colaboradores a identificaram como Pmc21, grupo esse nãocentrossimetrico (M1) e passou a ser Pbcm (M2), para temperaturas abaixo do ponto de Curie[41][42][43][44].Todavia, existem incertezas em torno da estrutura da fase correta, por não terem sido determinadas conclusivamente. Dessa forma, estudos teóricos revelam que ambas as fases antiferroelétricas e ferroelétricas com os grupos Pbcm e Pb21m, respectivamente, podem existir nesse sistema na temperatura ambiente.…”
unclassified
See 1 more Smart Citation